Kearifan Lokal Desa Nanasan - Titin Kholisna; Lutfiatus Zuhro; Nurul Lail Rosyidatul Muammaroh; Abdul Latif; R.R. Hesty Setyodyah Lestari; Muhammad Nafi’ (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2024)
The local wisdom is capital for every resident so that they are able to survive and survive. Each village offers a variety of beauty, such as the hamlet of Nanasan which implies natural tourism potential as well as beautiful and interesting culture. Our psychology study program at Raden Rahmat Islamic University implements the tridharma of service in participatory programs in efforts to build and develop villages in Nanasan hamlet. The abundant natural wealth that we found is coffee, clove, ginger and sweet potato plantations. Including natural tourism in beautiful valleys accompanied by dance culture and customs which are always enlivened in celebratory ceremonies. The urgency of this service is how residents are aware of continuing to strive to protect and care for nature through developing human resources through useful education. Keywords: local wisdom, nanasan village